Determinasi Keputusan Menabung Masyarakat pada Produk Tabungan Haji di Bank Syariah Indonesia Kota Medan - Faddila, Luthfiya; Zulhendry, Zulhendry; Nasution, Anriza Witi; Supaino, Supaino; Seri, Ermyna (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study was conducted to determine the effect of Product Innovation, Service Quality, and Knowledge on People's Decision to Save in Hajj Savings Products at Bank Syariah Indonesia in Medan. In this study, there are independent variables, namely Product Innovation, Service Quality, and Knowledge, as well as a dependent variable, namely the Decision to Save. Primary data in this study were obtained through questionnaires distributed to customers at Bank Syariah Indonesia in Medan who had used Hajj Savings Products, with a sample size of 100 respondents. This study used a quantitative method with a Likert scale instrument. The data were processed using the SPSS 26 program using multiple linear regression analysis techniques. Based on the results of the partial test, it shows that Product Innovation, Service Quality, and Knowledge partially have a positive and significant effect on the Decision to Save. Similarly, simultaneously, Product Innovation, Service Quality, and Knowledge have a positive and significant effect on the Decision to Save for the Hajj Savings Product at Bank Syariah Indonesia in Medan.